2013
DOI: 10.1182/blood-2013-03-488080
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of disease-causing GATA1 mutations in murine gene complementation systems

Abstract: Missense mutations in transcription factor GATA1 underlie a spectrum of congenital red blood cell and platelet disorders. We investigated how these alterations cause distinct clinical phenotypes by combining structural, biochemical, and genomic approaches with gene complementation systems that examine GATA1 function in biologically relevant cellular contexts. Substitutions that disrupt FOG1 cofactor binding impair both gene activation and repression and are associated with pronounced clinical phenotypes. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 51 publications
1
37
2
Order By: Relevance
“…However, several disease-associated amino acid substitutions within the N-finger inhibit GATA1 binding to target genes in vivo, yet have no effect on in vitro binding to naked DNA templates. These regions of the N-finger do not interact with DNA directly, but rather are believed to promote GATA1 chromatin occupancy by recruiting essential cofactors, including FOG1 and the TAL1/LMO2/LDB1 complex (35,38). Similarly, loss of the Kruppel-like factor 3 transcription N-terminus, which also does not bind DNA directly, alters chromatin occupancy selectively at a subset of in vivo target genes in mouse embryonic fibroblasts (54).…”
Section: Methodsmentioning
confidence: 99%
“…However, several disease-associated amino acid substitutions within the N-finger inhibit GATA1 binding to target genes in vivo, yet have no effect on in vitro binding to naked DNA templates. These regions of the N-finger do not interact with DNA directly, but rather are believed to promote GATA1 chromatin occupancy by recruiting essential cofactors, including FOG1 and the TAL1/LMO2/LDB1 complex (35,38). Similarly, loss of the Kruppel-like factor 3 transcription N-terminus, which also does not bind DNA directly, alters chromatin occupancy selectively at a subset of in vivo target genes in mouse embryonic fibroblasts (54).…”
Section: Methodsmentioning
confidence: 99%
“…In several Mendelian erythroid disorders (MEDs), NC genetic variants have been identified in the DNA-binding motif (WGATAR) of the hematopoietic master regulator, GATA1 (20)(21)(22)(23)(24)(25). GATA1 is both necessary for proper erythropoiesis (3,26) and sufficient to reprogram alternative lineages toward an erythroid fate (27,28). Moreover, numerous studies have shown that GATA1 acts in a…”
Section: Mendelian Erythroid Disordersmentioning
confidence: 99%
“…7A, middle; Supplemental Fig. S10B), including a-globin, b-globin, Alas2, and Gypa, whose transcription is known to be FOG1-dependent (Crispino et al 1999;Anguita et al 2004;Letting et al 2004;Pal et al 2004; Campbell et al 2013). FOG1 occupied these genes or their regulatory regions in cells expressing LDB1 FL but was significantly decreased in cells expressing LDB1D4/5 (Fig.…”
Section: Ldb1-regulated Genes That Are Sensitive To the Deletion Of Lmentioning
confidence: 99%